Pemberdayaan UMKM melalui Digitalisasi Promosi Visual dan Integrasi Google Maps untuk Penguatan Pemasaran Lokal di Desa Kembang Kerang - Muhammad Saiful; Amri Muliawan Nur; Desi Safitri; Era Fazira; Amir Bagja; Rodianto (Universitas Hamzanwadi, 2026)
Micro, small, and medium enterprises (MSMEs) play a significant role in supporting local economic development; however, many business owners still face marketing challenges due to limited utilization of digital technology. This community service program aimed to enhance MSME marketing capacity through visual promotion digitalization and Google Maps integration for Tahu Bunda Ririn MSME in Kembang Kerang Village, Aikmel District, East Lombok Regency. The implementation methods included observation, interviews, needs analysis, development of visual promotional media in the form of banners and posters using Canva, assistance in creating a Google Maps business profile, and activity evaluation. The results demonstrated that the MSME successfully established a business profile integrated with Google Maps, enabling customers to easily locate the business and access business information digitally. Furthermore, the promotional banners and posters improved the visual identity and attractiveness of the business to the community. The assistance program also enhanced the UMKM owner's digital literacy and understanding of technology utilization for marketing purposes. Overall, the program successfully increased business visibility, strengthened local marketing efforts, and created opportunities for broader market expansion through digital technology adoption. This empowerment model can serve as an alternative technology-based strategy for UMKM development that is practical and applicable in rural areas.